Prevalence and determinants of osteoporosis in patients with type 1 and type 2 diabetes mellitus - Leidig-Bruckner, Gudrun; Grobholz, Sonja; Bruckner, Thomas; Scheidt-Nave, Christa; Nawroth, Peter Paul; Schneider, Jochen G. (BMC endocrine disorders, 2014)
Increased risk of osteoporosis and its clinical significance in patients with diabetes is controversial. We analyze osteoporosis prevalence and determinants of bone mineral density (BMD) in patients with type 1 and 2 diabetes.